Knowledge of the Human Monkey Pox Infection among Medical Practitioners in Punjab, Pakistan - Dr. Romaisa Khalid; Dr.Sumera Ehsan; Ayesha Khalid; Dr. Khalid Mahmood (Aziz Fatimah Medical and Dental College, 2022)
Objective: To assess the knowledge of medical practitioners regarding The Human Monkey Pox Infection. Methodology: A cross sectional study was performed between June 2022 and August 2022 among medical practitioners in Punjab, Pakistan especially the medical practitioners from major cities including Lahore, Faisalabad, Multan. Data was collected through an online, self-administered questionnaire. Piloting was done and feedback was taken. All the registered doctors working in different areas of Pakistan were included in this study. All non-registered doctors, nurses and paramedical staff were excluded from this study. Ethical approval was taken from the Office of the Ethical Review Committee, Faisalabad Medical University, Letter number: 48-ERC/FMU/2021-2022/232. Data was analyzed using SPSS version20.0. Results: Out of the 250 participants, 52(20.8%) were house officers, 78(31.2%) were medical officers,78(31.2%) were postgraduate residents and 16.8% were consultants. Among 250 participants, 170(68%) were in between the ages of 23 to 33, 16.4% between 34 to 44 and 39(15.6%) were between 45 to 55 years of age. Our 229(91.6%) participants were aware of The Human Monkey Pox Infection [HMPI] and 8.4% were not aware of HMPI. Only 115(46%) participants consider HMPI similar to smallpox. Majority of the respondents were aware of the predominant symptoms of the HMPI. Only 116(46.4%) participants consider 2nd and 3rd generation small pox vaccines to be effective against The Human Monkey pox Virus [HMPV]. Conclusion: This study shows the knowledge of medical practitioners is relatively low. But considering the fact as being a newly emerging disease in Asian countries the overall response of doctors was a bit reasonable. Due to high alert by WHO there is an utmost need of training sessions for medical practitioners.